DEVELOPMENT OF PARENTING SKILLS IN A SCOPE OF GROUP SOCIAL WORK - Anahit Sahakyan; Anna Voskanyan; Liana Mkrtchyan (Banber Erevani Hamalsarani. Sots'iologia, 2024)
Parenting skills play a crucial role in shaping children's development and well-being. This aticle presents a comprehensive review of the literature and research on the development of parenting skills, focusing on various factors influencing parenting practices, interventions aimed at enhancing parenting skills. In order to study the native experience of developing parenting skills, the program of group work implemented in 2022-2023 in "Shogh" community-based children's day centers operating under the Armenian Missionary Association of America (AMAA) was presented. The mission of the researched project was to form a conscious and positive approach to parenting in Armenia, and the goal was to develop the parenting knowledge and skills of parents of school-age children. For its evaluation, 2 main methods were used: "Before and after" evaluation and "The most significant change" survey, after which a quantitative and qualitative analysis of the obtained results was performed. The authors argue that a review of both theoretical and research literature indicate that the development of parenting skills has a direct impact on the child's socio-psychological development, on the dynamics of family relationships and, in general, on the child's well-being and social responsibility.